KEGIATAN SALAT DUHA DI MI AL-HUDA KARANGNONGKO SEBAGAI IMPLEMENTASI KAJIAN LIVING HADIS - Ahmad Royhan Anwar; Muhammad Aufal Minan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2022)
Duha prayer is one of the sunnah prayers highly recommended by the Prophet SAW. Scholars and even the Prophet SAW once said that there are many virtues and privileges for those who carry it out, both two rak'ahs, or the rest. This study aims to determine the implementation of Duha prayer activities at MI Al-Huda Karangnongko as the implementation of living hadith studies. The method used in this research is using descriptive analytical method with a qualitative approach. The results showed that in the implementation of Duha prayer activities in this school, the role of the educator was no longer as a learning center, but as a facilitator and giver of direction in the process of implementing activities. The driving factor for holding this activity is the habituation of students as well as the hadith that explains that the reward and goodness of the Duha prayer are the same as the implementation of alms, while the inhibiting factors are the lack of student interest, parental support, facilities, student discipline, and the existence of a pandemic. For advice, educators should be more optimal in coordinating or controlling the course of activities and immediately looking for solutions to all existing inhibiting factors in order to achieve the desired results.